Penerapan Etika Komunikasi Reception Pada Divisi Kantor Depan Dalam Pelayanan Tamu Check In Di Javana Royal Vila Seminyak Bali - Setiawan, Muhamad Alam; Muharis; Afandi, Satria (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
The Increasing competition among accommodation supplies require it to keep optimizing its services in order to give the impression of loyalty to guests to stay. In more specific case, receptionists hold important rules to improve their services, especially in communication ethics. This study is conducted in Javana Royal Villa Seminyak Bali, under the title of Penerapan Etika Komunikasi Reception Pada Front Office Department Dalam Pelayanan Tamu Check in di Javana Royal Villa Seminyak. Bali. This research aims to determine the application of reception communication ethics and the influence of the application of reception communication ethics toward room occupancy rate at Javana Royal Villa Seminyak Bali. This study uses qualitative descriptive in which the translation of words or sentences are explained in the presentation. Moreover, the data collection techniques used are observation, interviews and documentation. The types of data used are primary data and secondary data. The study showed that by not concerning attention to communication ethics, it will greatly impact the comfort of guests in staying which results in bad reviews on the online travel agent so that in this case it certainly has a huge impact on the level of room reservations or on room occupancy in Javana Royal Villa Seminyak Bali.